Gastric-type adenocarcinoma of the cervix in patients with Peutz-Jeghers syndrome: a systematic review of the literature with proposed screening guidelines. Issue 1 (13th December 2021) - Gordhandas, Sushmita B; Kahn, Ryan; Sassine, Dib; Aviki, Emeline M; Baltich Nelson, Becky; Catchings, Amanda; Liu, Ying L; Lakhman, Yuliya; Abu-Rustum, Nadeem R; Park, Kay J; Mueller, Jennifer J
Abstract : Objectives: To perform a systematic review of gastric-type adenocarcinoma of the cervix and lobular endocervical glandular hyperplasia (a possible precursor lesion) in Peutz-Jeghers syndrome, and to analyze data from the literature, along with our institutional experience, to determine recommendations for screening and detection. Methods: A comprehensive literature searc and retrospective search of pathology records at our institutio were conducted. Articles were screened by two independent reviewers. Case reports/series on lobular endocervical glandular hyperplasia/gastric-type adenocarcinoma of the cervix in Peutz-Jeghers syndrome were included. Demographic, clinical, and radiologic information was collected. Results: A total of 1564 publications were reviewed; 38 met the inclusion criteria. Forty-nine were included in the analysis (43 from the literature, 6 from our institution). Forty-three reported on gastric-type adenocarcinoma alone, 4 on lobular endocervical glandular hyperplasia alone, and 2 on concurrent lobular endocervical glandular hyperplasia/gastric-type adenocarcinoma. Median age at diagnosis was 17 (range, 4–52) for patients with lobular endocervical glandular hyperplasia alone and 35 (range, 15–72) for those with gastric-type adenocarcinoma. The most common presenting symptoms were abdominal/pelvic pain and vaginal bleeding/discharge. Imaging was reported for 27 patients; 24 (89%) had abnormal cervical features. Papanicolaou (Pap) smear prior to diagnosis was reported for 12 patients; 6 (50%) had normal cytology, 4 (33%) atypical glandular cells, and 2 (17%) atypical cells not otherwise specified. Patients with gastric-type adenocarcinoma (n=45) were treated with surgery alone (n=16), surgery/chemotherapy/radiation (n=11), surgery/chemotherapy (n=9), surgery/radiation (n=5), or radiation/chemotherapy (n=4). Twelve (27%) of 45 patients recurred; median progression-free survival was 10 months (range, 1–148). Twenty patients (44%) died; median overall survival was 26 months (range, 2–156). Thirteen patients (27%) were alive with no evidence of disease. Conclusions: Gastric-type adenocarcinoma in Peutz-Jeghers syndrome is associated with poor outcomes and short progression-free and overall survival. Screening recommendations, including pathognomonic symptom review and physical examination, with a low threshold for imaging and biopsy, may detect precursor lesions and early-stage gastric-type adenocarcinoma, leading to better outcomes in this high-risk population. PROSPERO registration number: CRD42019118151